Enhancing language teaching and learning with technology for communicative competence - Lecomte, Michelle (Univerzita Pardubice, 2018)
Digital technologies have impacted the way that most people live, work, and study in the 21st century. These technologies have greatly impacted and influenced the expected key competencies for modern learning and modified the classrooms of many language teachers. The purpose of this thesis is to examine how a language teacher can best design tasks, keeping all the necessary aspects in mind. The theoretical section analyses three main components of a contemporary language lesson: communicative competence, pedagogy, and digital technologies. Each section will produce purposeful questions to aid the teacher in making decisions for the implementation of digital aids, a framework model. This framework will then be applied to a hypothetical university classroom setting. Six language tasks have been designed to test the framework and assess its usefulness, with a final evaluation.
Rozvoj komunikační kompetence ve výuce anglického jazyka prostřednictvím moderních technologií
Keywords: komunikativní kompetence; digitální technologie; pedagogika; autentické úkoly; communicative competence; digital technology; pedagogy; authentic tasks